KECERDASAN EMOSI SISWA PADA PENINGKATAN HASIL BELAJAR IPS MELALUI BELAJAR KOOPERATIF DI SD LABORATORIUM UNG - Elmia Umar (Psympathic : Jurnal Ilmiah Psikologi, 2014)
The objective of this research is to know the learning process to increase elementary student outcomes in social science study through the cooperative learning and whether there was an increase after the action. About 20 students of School Laboratories, State University of Gorontalo were the subject of research. The research used action research method with data collecting technique including field notes, interview, documentation and observation. The result of the research describes that the cooperative learning in social science study gives impact for increasing social science learning of elementary school proved by increasing of score test average by 85% and the result in observation showed by 80% from the total number of student.